2007
DOI: 10.1089/jpm.2006.0135
|View full text |Cite
|
Sign up to set email alerts
|

National Survey of Pediatric Residency Program Directors and Residents Regarding Education in Palliative Medicine and End-of-Life Care

Abstract: For palliative care principles to be better incorporated into pediatric practice, they must be incorporated into residency education, optimally through informal teaching and during rounds. Finding ways to teach residents palliative medicine during clinical "teachable moments" and standardizing didactic curricula should become a priority in palliative and end-of-life care education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 18 publications
3
69
0
1
Order By: Relevance
“…Compared to other studies, these results are likely an accurate reflection of the comfort level of fellows and the palliative care education that has been provided-in terms of hours and type of education, and the number of patients who die who are cared for by pediatric residents and fellows. 4,[6][7][8][9][10] There are several limitations to this study. Selection bias could play a part in fellows that completed the survey, and hence we would exercise caution when citing these results to make generalizations about the state of palliative care education in pediatric residencies and fellowships.…”
Section: Discussionmentioning
confidence: 98%
“…Compared to other studies, these results are likely an accurate reflection of the comfort level of fellows and the palliative care education that has been provided-in terms of hours and type of education, and the number of patients who die who are cared for by pediatric residents and fellows. 4,[6][7][8][9][10] There are several limitations to this study. Selection bias could play a part in fellows that completed the survey, and hence we would exercise caution when citing these results to make generalizations about the state of palliative care education in pediatric residencies and fellowships.…”
Section: Discussionmentioning
confidence: 98%
“…25 In spite of the need for more EOL education, postgraduate medical instruction for residents caring for terminally ill patients has traditionally remained very low. 12,[26][27][28][29] The lack of teaching about palliative care is ironic since it is during residency that most pediatricians must first assume primary responsibility for terminally ill patients. In fact, studies report discordance between the large number of dying children cared for during pediatric residency training and the scant emphasis placed on EOL education.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,[8][9][10][11] A recent national survey of pediatric residency program directors revealed that less than one third have no faculty available to teach palliative care, and less than 40% of survey participants believed that matriculating residents are competent in palliative medicine. 12 During the academic year 2000-2001, pediatric house staff in the Pediatric Residency Training Program at the Stanford University School of Medicine cared for more than 120 children and adolescents who died (an average of 2 patients per resident). Similar to other training programs across the country, no formal palliative care curriculum existed in our program at the time.…”
mentioning
confidence: 99%
“…[1][2][3] Despite recognizing the need to incorporate EOL education and palliative care into residency, 4-6 most pediatrics programs do not have a formal curriculum in EOL, especially in institutions where a pediatric palliative care service is not available.…”
Section: Introductionmentioning
confidence: 99%